The Optical Tricks Experience in virtual studios on the Algerian Television An Applied Approach - Selami Saidani; Leila Feguiri (Journal of Science and Knowledge Horizons, 2025)
The study focuses on the transition from traditional set design to the use of virtual studios and computer-generated decor. The research problem stems from the ongoing challenge of balancing rising production costs with the creative opportunities offered by virtual technologies. Despite remarkable technological progress, real shooting locations and physical sets continue to impose significant financial burdens on television institutions. This research aims to analyze how virtual studio and decor technologies enhance economic efficiency within television institutions. It also seeks to examine how Algerian television applies key economic and managerial principles, such as planning, organization, and budgeting, in adopting these technologies. Finally, the study proposes a strategic management framework designed to improve audiovisual production processes through the effective integration of virtual technologies